Bone chase - Ochse, Weston (Saga Press, 2020)
"In true The Da Vinci Code fashion, a taut thriller filled with rival factions vying for control of the truth in a giant global conspiracy. There were giants on the earth in those days-at least that's what the Bible says. But, where are they? Did they ever really exist at all? When out-of-work math teacher Ethan McCloud is sent a mysterious box, he and his ex-girlfriend begin to unravel a mystery 10,000 years in the making-and he is the last hope to discovering the world's greatest conspiracy. Chased by both the Six-Fingered Man and the Council of David, Ethan must survive the chase-and find the truth"--